Β‐Methylphenylethylamines: common fragmentation pathways with amphetamines in electrospray ionization collision‐induced dissociation. Issue 3 (26th May 2015) - Brown, David H.; Hansson, Robert; Oosthuizen, Francois; Sumner, Nathan
Abstract : β ‐Methylphenylethylamines are positional isomers of amphetamines and have been discovered in sporting supplements. Although the fragmentation of the β ‐methylphenylethylamine and N‐methyl‐ β ‐methylphenylethylamine in gas chromatography‐electron ionization‐mass spectrometry (GC‐EI‐MS) systems is significantly different to their amphetamine and methylamphetamine isomers, under electrospray ionization commonly used in liquid chromatography‐mass spectrometry (LC‐MS) systems, the fragmentation of each of the isomeric pairs is almost identical. The similarities in fragmentation make it possible for the misidentification of the β ‐methylphenylethylamines as the illicit amphetamines. It is proposed that the similarities are due to a fragmentation pathway involving a common phenonium ion intermediate. By careful control of fragmentation energies in liquid chromatography‐tandem mass spectrometry (LC‐MS/MS) systems and/or close examination of the relative abundances of product ions formed by collision‐induced dissociation (qualifier ratios), it is possible to distinguish the β ‐methylphenylethylamines from the amphetamines, even if significant retention time separation is not achieved. In liquid chromatography‐electrospray ionization‐quadrupole time of flight (LC‐ESI‐QTOF) systems the mass spectra of the β ‐methylphenylethylamines are identical to their amphetamine isomers. In such systems, retention time separation of the isomers is critical to avoid misidentification. During this study β ‐methylphenylethylamine and N‐methyl‐ β ‐methylphenylethylamine have been identified in commercially available sporting supplements and oral fluid samples taken during the course of road‐side drugs‐in‐drivers and workplace testing programmes. Copyright © 2015 John Wiley & Sons, Ltd. Abstract : It is proposed that beta‐methylphenylethylamines and amphetamines share a common fragmentation pathway via a phenonium ion under electrospray ionization collision‐induced dissociation resulting in almost identical fragmentation patterns. Without retention time separation or careful observation of qualifier ratios then the β ‐methylphenylethylamines may get misidentified as amphetamines.